Bibliotekininkas mokslininkas Kazys Sendzikas - Lietuvninkaitė, Nijolė (Knygotyra, 1996)
The subject fields of the science collection of Vaclovas Biržiška, and its importance for the scientific, pedagogical, and practical activities of this famous bibliographer, have been investigated. Vaclovas Biržiška compiled a collection of books of about 5,000 copies. In 1944, this collection was moved to Kaunas University Library. After the reorganization of Kaunas University in 1950, the collection was distributed to several institutions. At present, approximately 2,000 copies of this collection are in the Library of Kaunas University of Technology, and about 1,000 copies are in the Vilnius University Library. We may find books from this collection in other major Lithuanian libraries as well. Vaclovas Biržiška collected approximately 300 key theoretical and historical works on book science published in Poland, Russia, Germany, and other countries from the 19th century to the first part of the 20th century. The collection was composed of books and periodicals on book history, bibliography, and librarianship. Vaclovas Biržiška had a significant collection on book history, including works on incunabula, book art, the collection of rare and valuable books, and other literature. He also collected bibliography science and history, including works on Russian, Polish, and German national bibliography. The renowned German scientist G. Schneider, with his bibliography theory, exerted a significant influence on Vaclovas Biržiška’s work and Lithuanian bibliography in general. Biržiška gathered many different bibliographical lists (indexes). The acquisition of works on book science is connected to Vaclovas Biržiška’s role as the director of Kaunas University Library. He ensured the applicability of experiences from foreign countries. The acquisition of his personal library was related to his professional needs. He used this collection for studies, investigations, and in articles for the Lietuviškoji enciklopedija. The most important bibliographers’ works were reviewed by Vaclovas Biržiška in journals such as Knygos, Baras, and Bibliografijos žinios. The book science literature was useful when he started teaching book history and bibliography at Kaunas University. Vaclovas Biržiška adapted the experience of foreign libraries to his library activities. The book science collection was a very important supplement to the scientific and practical activities of Vaclovas Biržiška.